"EVIDENCE” AND BIOMEDICINE - Rodríguez Allen, Ana (2018)
This article demonstrates that the justifcation of the dominant medical focus, stating its activities are scientifc because they require the evidence of proof, that is in many cases observational, is an act of faith that is ultimately completely anachronistic in comparison to the contemporary scientifc debates.